Dynamic responses of plates and slabs due to impact loads - Chong, Chee Siang (2018)
Impact phenomenon is a multidisciplinary subject and is of interest for all engineering, physics, aerospace, space, defense, building and auto industries. The present study involves analysis, experimentation using LabVIEW and Finite Element Method (FEM) simulation using Abaqus software for structural members such as beams and slabs. During the service life of the structure, the structural members might be subjected to impact loads. In order to develop a protective structure that is capable of withstanding the potential percussion, the relevant impact engineering studies are stimulated. Plates and slabs are the major elements of most of the structures. Steel plates are commonly used in manufacturing and have high potential to competently resist the impact load. Also reinforced concrete (RC) slab is widely used in the construction industry. Thus, the dynamic responses of the steel plates and RC slabs due to impact load were investigated in this study. The conventional analytical method, Hertz's contact theory, Navier's solution and Levy's solution were reviewed and formulated for analysing the impact responses of steel plates and RC slabs. Hammer drop test is the usual approach that is conducted to examine the impact responses of steel plates and RC slabs. The finite element professional software package Abaqus version 6.12 was used to model and simulate the response of the steel plate and RC slab in the aforementioned experiments. Since the response of plates and slabs depends on the material properties, mode of impact, the transmitted impact forces, aspect ratio of the specimens, span and boundary conditions, experiments were conducted on 58 steel plate models and 24 RC slab models with various hammer heights, specimen aspect ratios, support spans and support conditions. The experimental responses of the steel plates and RC slabs in the hammer drop test were evaluated with a data acquisition system that consists of data acquisition and analysis hardware (National Instruments USB-6281 multifunction DAQ card), two units of 4-channel ICP @ sensor signal conditioner, six numbers of model 350303 PCB piezoelectric accelerometers and an application software (National Instrument LabVIEW software). These responses were also computed using Levy's solution and modelled with Abaqus simulation. The results of the experimental studies agree well with the analytical values as well as the FEM responses obtained using Abaqus simulation, thus validating the results. Using this validation and appropriate calibration, the virtual hammer drop test is developed using Abaqus software. It is highly potent to predict the impact responses of plates and slabs accurately. Thus, the concept of this virtual impact test can be further extended for general studies involving structures of general shape, size, impact energy, direction and mode of impact. This can be particularly useful to conduct virtual tests in situations where experimental tests are either not feasible or not economical to be carried out.